SISTEM PEMASARAN BERAS DI KECAMATAN CIBEBER, KABUPATEN CIANJUR - Alexandro Ephannuel Saragih; Netti Tinaprilla (Forum Agribisnis, 2015)
Rice is the basic commodity that becomes the staple food for Indonesian. The objectives of this research were to analyse marketing channels, function, structure and marketing institutions of rice farmer in Cibeber Subdistrict. In addition, the purposes of this research were to analyse the marketing efficiency using the marketing margin, farmer’s share and benefit cost ratio approaches. The research was conducted in 3 villages in Cisalak, Karangnunggal, Salamnunggal involving 30 farmers as respondents. 7 marketing institutions and 10 marketing channels are in the subdistrict. Generally, market structure in this subdistrict is oligopsonistic. Based on the marketing function and the profitable ratio of marketing cost, the most efficient channel is through farmers-middlemen-major collector and rice mills in village-retailer-consumer rice in Jakarta. The farmer should have made farmer groups as part of their marketing system in order to improve the bargaining position and easier capitalization through the warehouse system in Cianjur.